GE_GERICHTE P/1832/2015 vom 6. Februar 2017 - GE Cour de justice (2017)
ACCIDENT DE LA CIRCULATION ; LOI FÉDÉRALE SUR LA CIRCULATION ROUTIÈRE | LCR.90.1 LCR.26 CPP.398.4 LCR.34.4 OCR.12.1 LCR.35.3 LCR.35.5